Ability To Detect And First Aid Hypoglycaemia At Home In Patients With Type 2 Diabetes Mellitus - Siswanto, Hanifah Catur; Rachmawati, Dewi (Health Access Journal, 2024)
Hypoglycemia is an acute complication of diabetes mellitus patients that can occur repeatedly and can aggravate diabetes mellitus and even cause death. For this reason, first aid is needed to prevent death. This study aims to determine the ability to detect and first aid hypoglycemia at home in patients with type 2 diabetes mellitus. The research design used in this study is descriptive quantitative, with purposive sampling technique with a total of 30 respondents. The inclusion criteria are patients with type 2 diabetes mellitus who undergo both oral and insulin therapy. Data collection was carried out on April 03 until April 20, 2024. The research instrument used by giving a hypoglycemia detection ability questionnaire sheet consists of 5 knowledge questions, 4 attitude questions, 5 action questions, with an assessment of correct answers 1 and wrong answers 0. Then it is presented and categorized as very high (90 Until 100), high (80 Until 89), medium (65 Until 79), low (55 Until 64), and very low (0 Until 54). The results showed that the ability of patients with type 2 diabetes mellitus with very high ability was 37percent, high ability was 23percent, and moderate ability was 40percent. This study concluded that age, education, knowledge, and duration of diabetes mellitus can affect a person in detecting and first aid for hypoglycemia at home. From the results of this study on the ability to detect type 2 diabetes mellitus patients, it can be a study material and provide information for puskesmas in formulating plans as education on signs and symptoms, handling, and prevention of hypoglycemia through prolanis and posbindu PTM activities.